(untitled) (Italian Journal of Public Health, 2012)
Background: recent research shows that severe/very severe post-migration living difficulties (PMLD) have a negative impact on the mental health and social integration of refugees and asylum seekers. This study focuses on the role of PMLD in primary care “ordinary” immigrants. Methods: 443 primary care immigrants were asked to complete a self-administered questionnaire measuring the number and severity of pre-migratory potentially traumatic events (PTE), PMLD, and the current prevalence of a post-traumatic stress disorder (PTSD). The frequency of PMLD was assessed in the whole sample and compared in patients with and without PTSD. The effect of the number of PMLD on the risk of having a PTSD was studied by means of a regression analysis, adjusted by the number of PTE. Results: 391 patients completed the questionnaire and were enrolled into the study. The prevalence of PTSD was 10.2%. In the whole sample the most frequent PMLD were “no permission to work” (38.6%) and “poverty” (34.5%). All PMLD (except “communication difficulties”) were more frequent in patients with a PTSD. The number of PMLD significantly increased the likelihood to have a PTSD independently from PTE. Conclusions: severe/very severe post-migration living difficulties (PMLD) increase significantly the risk of PTSD in primary care “ordinary” migrants. Our hypothesis is that they have a retraumatizing effect on individuals who are already vulnerable and with a low capacity to handle resettlement stress due to their previous traumatic history. The implications in clinical practice and for immigration policies are discussed.